Complete Renal Artery Embolization in a Comorbid Patient with an Arteriovenous Malformation - Anthony Thayaparan; Tarik Amer; Eamon Mahdi; Omar Aboumarzouk; Owen Hughes (Case Reports in Urology)
Renal arteriovenous malformations are uncommon and are rarely a cause for presentation. However, they can occasionally pose life-threatening problems. We present a case of an elderly female who underwent a complete left renal artery embolization, following a difficult presentation complicated by advanced dementia and multiple comorbidities. This is the first documented case of complete renal artery embolisation used to treat a renal AVM.